Imbalances between supply and demand: Recent causes of labour shortages in advanced economies - Lisa Feist (International Labour Organization (ILO), 2024)
In the wake of the COVID-19 pandemic, numerous high-income countries encountered heightened vacancy rates and labour shortages, which persisted into 2023. This paper examines the dynamics underlying labour market fluctuations in advanced economies, such as cyclical movements, structural shifts and pandemic-induced trends. The surge in labour demand following economic reopening varied across sectors, as sustained fiscal support measures bolstered demand, contributing to a pronounced uptick in vacancies. Statistics on labour force participation and working hours highlight the intricacies of the supply side of the labour market. However, long-term projections reveal challenges stemming from population ageing, which were exacerbated by pandemic-induced retirements and gender disparities in employment. Shifts in migration patterns further shaped labour dynamics, with sectors such as healthcare, education, and information and communications technology grappling with skills shortages. Geographical mismatch and decreased labour mobility underscored the limitations in reallocating workers across regions. This analysis stresses the multifaceted nature of labour market challenges following the pandemic, urging policymakers to adopt nuanced strategies to address persistent labour shortages and structural transformations in advanced economies. This work is the result of background research in preparation of the ILO research department's 2024 WESO Trends report.
Keywords: 330; Employment; labor shortage; labor demand; labor supply; industrialized countries; Erwerbstätigkeit; Arbeitskräftemangel; Arbeitsnachfrage; Arbeitsangebot; Industrieländer